ANALISIS PENGARUH PAD, INVESTASI DAN BELANJA DAERAH TERHADAP TINGKAT KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI - Anggada, IGN Dharma (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 4 (2022): Vol. 11 No. 4, April 2022 [1215-1619]DO - 10.24843/EEP.2022.v11.i04.p05, 2022)
Poverty is a fundamental case that is experienced in every region in the Province of Bali which is of course the shared responsibility of both the regional government, the private sector as well as individual communities. The purpose based on this research is to analyze the impact of PAD, investment & regional expenditure on poverty levels in the Regency/City of the Province of Bali. The data source used is secondary data for 2016-2020. This research uses multiple linear regression analysis technique in the form of panei data. The resuIts according to this study show that PAD, investment & regional expenditure simultaneously affect the level of poverty in the Regency / City of Bali Province. For PAD & investment partially negative & insignificant effect on the poverty level in the Regency / City of Bali Province. Meanwhile, regional expenditure partially has a negative & significant effect on the poverty level in the Regency/City of the Province of Bali.